The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1042/cs20130186
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in hyperandrogenic polycystic ovary syndrome is not explained by either obesity or ectopic fat deposition

Abstract: PCOS (polycystic ovary syndrome) is associated with IR (insulin resistance), increased visceral fat and NAFLD (non-alcoholic fatty liver disease) all of which may contribute to endothelial dysfunction, an early marker of CVD (cardiovascular disease) risk. Our objective was to examine the relationships between endothelial dysfunction in PCOS, the volume of AT (adipose tissue) compartments and the size of intracellular TAG (triacylglycerol) pools in liver and skeletal muscle. A total of 19 women with PCOS (means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 43 publications
5
17
2
1
Order By: Relevance
“…Based on previously reported data (14,30), an absolute mean difference of Ն3.4% with a common standard deviation of 2.6% represents clinically relevant differences between groups. For the trial intervention, previously reported data (14,29) indicate that an absolute mean difference of Ն3.6% with a common standard deviation of 3.4% represents a clinically relevant improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previously reported data (14,30), an absolute mean difference of Ն3.4% with a common standard deviation of 2.6% represents clinically relevant differences between groups. For the trial intervention, previously reported data (14,29) indicate that an absolute mean difference of Ն3.6% with a common standard deviation of 3.4% represents a clinically relevant improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction is a key early step in the development of atherosclerosis (Celermajer et al 1992). It was well documented that endothelial dysfunction exists in subjects with PCOS (Lambert et al 2015, Srung et al 2014. Moreover, some studies have shown that endothelial dysfunction is partially dependent on inflammation and oxidative stress in PCOS (Pertynska-Vol.…”
Section: Introductionmentioning
confidence: 99%
“…; Sprung et al . ), and it has been reported that genetic female‐to‐male transsexuals taking high‐dose androgens exhibit impaired vascular smooth muscle reactivity (McCredie et al . ).…”
Section: Introductionmentioning
confidence: 99%